Different Effectiveness of Dry Needle with Laser After Myofascial Release Added on Complaints of Myogenous Back Pain - Saifudin Zuhri; Marti Rustanti (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Low back pain (LBP) complaints are prevalent that many people experience daily. Dry needling physiotherapy technology for myogenic LBP complaints has not been widely used in the clinical setting than laser. In contrast, it turns out that the application of laser for pain cases was not effectively socialized. In this study, the efficacy of dry laser needling was compared after the addition of myofascial release for myogenic LBP complaints. The research method was experimental study used two groups before and after the test design. The subjects were determined by reasoned sampling. The subjects were all patients with complaints of myogenic LBP who met the research criteria. The number of subjects in group I was 37 subjects, and group II was 36 subjects with myogenic LBP. The research was conducted from March to October 2020 at Sunafa physiotherapy practice, Colomadu, Karanganyar. There was a significant effect of dry needling with the myofascial release on pain reduction in patients with myogenic LBP (p=0,000). Also, there was a significant effect of laser with the myofascial release on pain reduction in patients with myogenic LBP (p=0,000). Dry needles and laser after adding myofascial release effectively reduce pain in patients with myogenic LBP.